Appraisals of Bangladeshi Medicinal Plants Used by Folk Medicine Practitioners in the Prevention and Management of Malignant Neoplastic Diseases. (14th January 2016) - Kabidul Azam, Md. Nur; Rahman, Md. Mizanur; Biswas, Samanta; Ahmed, Md. Nasir
Abstract : Cancer is a group of diseases which is categorized to differentiate into diverse cell types and move around in the body to sites of organogenesis that is key to the process of tumor genesis. All types of cancer fall into the group of malignant neoplastic diseases. In Bangladesh, cancer is now one of the foremost killer diseases and its personal, social, and economic bearing are huge. Plant-derived natural compounds (vincristine, vinblastine, etoposide, paclitaxel, camptothecin, topotecan, and irinotecan) are useful for the treatment of cancer. Since there is no extensive ethnobotanical research study in Bangladesh regarding the traditional uses of medicinal plants against neoplasms, therefore, a randomized ethnopharmacological surveys were carried out in 3 districts of Bangladesh to learn more about the usage of anticancer medicinal plants and their chemical constituents having antineoplastic activity. Comprehensive interviews were conducted to the folk medicine practitioners and medicinal plants as pointed out by them were photographed, collected, deposited, and identified at the Bangladesh National Herbarium. The various plant parts have been used by the healers which included whole plant, leaves, fruits, barks, roots, and seeds. This study evaluated considerable potential for discovery of novel compounds with less side effects in the management and prevention of malignancy in cancer.